Study of the neuronal response to olfactory stimuli in control and LPS-stimulated mice by functional magnetic resonance imaging - A. E. Akulov; A. V. Romashchenko; O. B. Shevelev; D. V. Petrovski; A. A. Savelov; M. P. Moshkin (Вавиловский журнал генетики и селекции)
Olfactory perception plays the key role in the interaction of animals with biotic factors of the species-specific econiche. Identification of odorants informs nocturnal animals about social environment, presence of predators, or infected food. Olfactory efficiency depends on physiological conditions; in particular, odor sensitivity can be changed by infection. This work considers use of fMRI in the study of the influence of innate immunity activation on neuronal response during perception and differentiation of socially significant (2.5-dimethylpyrazine, 2-heptanon) and socially insignificant (1-hexanol and isoprene) olfactory stimuli by CD-1 mice. We stimulated innate immunity by intraperitoneal injection of bacterial lipopolysaccharide (LPS) at the dose 500 µg/kg three hours before tomography. Urethane anesthesia was used during MRI trail. Odor stimulation was done with a lab-made metering unit for supplying standard doses of volatile organic compounds. The supply of olfactory stimuli induced activation of neurons in the primary perceptual center and the centers of secondary processing of olfactory information. Olfactory stimulus type affected neuronal response rate in an olfactory bulb but did not affect response parameters in other brain regions studied. This increase in neuronal activity is likely to be of adaptive significance as a mechanism supporting olfactory sensitivity increase, which plays the key role in the identification of potential sources of infection.